Nanotechnology and Nanomedicine: A Promising Avenue for Lung Cancer Diagnosis and Therapy - Wei Yin; Feng Pan; Junjie Zhu; Junwu Xu; Diego Gonzalez-Rivas; Meinoshin Okumura; Zhiyong Tang; Yang Yang (Engineering, 2021)
Lung cancer is a leading cause of cancer-related death worldwide, with a very poor overall five-year survival rate. The intrinsic limitations associated with the conventional diagnosis and therapeutic strategies used for lung cancer have motivated the development of nanotechnology and nanomedicine approaches, in order to improve early diagnosis rate and develop more effective and safer therapeutic options for lung cancer. Cancer nanomedicines aim to individualize drug delivery, diagnosis, and therapy by tailoring them to each patient’s unique physiology and pathological features—on both the genomic and proteomic levels—and have attracted widespread attention in this field. Despite the successful application of nanomedicine techniques in lung cancer research, the clinical translation of nanomedicine approaches remains challenging due to the limited understanding of the interactions that occur between nanotechnology and biology, and the challenges posed by the toxicology, pharmacology, immunology, and large-scale manufacturing of nanoparticles. In this review, we highlight the progress and opportunities associated with nanomedicine use for lung cancer treatment and discuss the prospects of this field, together with the challenges associated with clinical translation.